2021
DOI: 10.3390/pathogens10050532
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Effect of the Total Glycosides of the Medicinal Plant, Ranunculus japonicus

Abstract: In traditional Chinese medicine, Ranunculus japonicus has been used to treat various diseases, including malaria, and the young stem of R. japonicus is consumed as a food in the Republic of Korea. However, experimental evidence of the antimalarial effect of R. japonicus has not been evaluated. Therefore, the antimalarial activity of the extract of the young stem of R. japonicus was evaluated in vitro using both chloroquine-sensitive (3D7) and chloroquine-resistant (Dd2) strains; in vivo activity was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…is one kind of traditional Chinese medicines with a long history and has been reported to have pharmacological activities, such as anti-inflammatory, analgesic, and other effects. [20][21][22] Our screening from a TCMs pool for anti-HBV activities showed the ethanol extract of R. japonicus Thunb. could inhibit the production of HBeAg and showed anti-HBV potency.…”
Section: R Japonicusmentioning
confidence: 99%
“…is one kind of traditional Chinese medicines with a long history and has been reported to have pharmacological activities, such as anti-inflammatory, analgesic, and other effects. [20][21][22] Our screening from a TCMs pool for anti-HBV activities showed the ethanol extract of R. japonicus Thunb. could inhibit the production of HBeAg and showed anti-HBV potency.…”
Section: R Japonicusmentioning
confidence: 99%
“…Since then, studies have demonstrated various phytomedicinal activities, such as the protective effect on heart diseases including myocardial ischemic-reperfusion injury, hypertrophy in cardiomyocytes, and high blood pressure by alleviating chronic [Ca 2+ ] i overload, as well as therapeutic effects on rheumatoid arthritis and decreasing intracellular [Ca 2+ ] i in vascular smooth muscle cells [50,57,58]. In addition, R. japonicus extracts showed antimalarial effects in in vitro culture of Plasmodium falciparum and in vivo rodent malaria experimental systems of Plasmodium berghei [56].…”
Section: Ranunculus Japonicus Thunbmentioning
confidence: 99%
“…Inhibits migration capacity of rheumatoid arthritis fibroblast-like synoviocytes methanolic extract of whole plant [50] Antimalarial Inhibits parasite growth in Plasmodium falciparum and P. berghei improve hepatic and renal parameters ethanolic extract of whole plant [56] Antihypertrophic Suppresses elevated expression of the ANP, BNP, and beta-MHC inhibits up-regulation of [Ca 2+ ] i total glycosides of whole plant [57] Protective effect of myocardial ischemicreperfusion injury…”
Section: Antirheumatoid Arthritismentioning
confidence: 99%
“…L. Fu et al, 2013;Luo et al, 2022;Z. Y. Wang et al, 2021;Yun et al, 2021). Many chemical substances have been extracted and isolated from R. japonicus, including flavonoids, lactones, chromones, terpenoids, phenolic acids, and alkaloids (Na, 2015;Zhong & Feng, 2011).…”
Section: Introductionmentioning
confidence: 99%